Harmful effects behind the daily supplementation of a fixed vegetarian blend in the rat model. (November 2016) - Bonamassa, Barbara; Canistro, Donatella; Sapone, Andrea; Vivarelli, Fabio; Vornoli, Andrea; Longo, Vincenzo; Paolini, Moreno
Abstract: Fruit and vegetables (FV) have long been considered a panacea against major chronic diseases, including cancer. However, there is no convincing epidemiological, clinical or experimental evidence supporting FV chemopreventive ability. A daily mono-supplementation of lyophilized onion, tomato, peach, black grape or lettuce was compared with the daily combined administration of the same FV (5 a day-like diet). Ten days post-treatment, the phase-I/II xenobiotic metabolizing and antioxidant enzyme activities, protein and mRNA levels were investigated. As a marker of oxidative stress, the level of hydroperoxides was measured in rat serum samples. Here we show that a blend of FV orally administered to rats not only potentially manipulates metabolism but also disrupts systemic oxidative homeostasis. A daily combination of the five servings remarkably down-regulates the catalytic activity, protein and mRNA levels of a cohort of hepatic metabolizing enzymes, suggesting a possible depressed clearance upon exposure to ubiquitous carcinogens. Strikingly, we observed an impairment of antioxidant enzymes with a boost in systemic hydroperoxide levels. Our study identifies new potential factors of cancer risk connected with the persistent consumption of fixed servings of FV, suggesting that dietary guidance should rely on a "daily diversification" of FV. Highlights: The chemopreventive role of a "5 a day"-like diet supplementation and its five individual constituents was assessed in rats. The "5 a day"-like and lettuce-based supplementations caused a complex modulation of XMEs and oxidative homeostasis impairment. Phase-I enzymes were down-regulated. Oxidative stress measured as levels of hydroperoxides was significantly boosted. Caution is needed when mono-diets or the same fixed blend of FV consumption is recommended.